Comparison of modern locked plating and antiglide plating for fixation of osteoporotic distal fibular fractures. Issue 3 (September 2016) - Switaj, Paul J.; Wetzel, Robert J.; Jain, Neel P.; Weatherford, Brian M.; Ren, Yupeng; Zhang, Li-Qun; Merk, Bradley R.
Highlights: Locked plate was compared to antiglide plate in an osteoporotic ankle fracture. Locked plate had significantly higher torque to failure and construct stiffness. Locked plate failed through the distal locking screws. Antiglide plate failed through screw pullout and fracture displacement. Locked plate may provide stronger option in osteoporotic distal fibula fractures. Abstract: Background: Fractures in osteoporotic patients can be difficult to treat because of poor bone quality and inability to gain screw purchase. The purpose of this study is to compare modern lateral periarticular distal fibula locked plating to antiglide plating in the setting of an osteoporotic, unstable distal fibula fracture. Methods: AO/OTA 44-B2 distal fibula fractures were created in sixteen paired fresh frozen cadaveric ankles and fixed with a lateral locking plate and an independent lag screw or an antiglide plate with a lag screw through the plate. The specimens underwent stiffness, cyclic loading, and load to failure testing. The energy absorbed until failure, torque to failure, construct stiffness, angle at failure, and energy at failure was recorded. Results: The lateral locking construct had a higher torque to failure ( p  = 0.02) and construct stiffness ( p  = 0.04). The locking construct showed a trend toward increased angle at failure, but did not reach statistical significance ( p  = 0.07). Seven of the eight lateral locking plate specimens failed through the distal locking screws, while the antiglide plating construct failed with pullout of the distal screws and displacement of the fracture in six of the eight specimens. Conclusion: In our study, the newly designed distal fibula periarticular locking plate with increased distal fixation is biomechanically stronger than a non-locking one third tubular plate applied in antiglide fashion for the treatment of AO/OTA 44-B2 osteoporotic distal fibula fractures. Level of evidence: V: This is an ex-vivo study performed on cadavers and is not a study performed on live patients. Therefore, this is considered Level V evidence.